Effect of Job Training and Commissions on the Performance of General Insurance Agents (Case Study at PT Asuransi Allianz Utama Indonesia Semarang Branch) - Malebra, Irawan -; Kurniani, Kurniani -; Safitri, Anis - (Admisi dan Bisnis, 2023)
The research aims to understand the influence of job training and commission on the performance of general insurance agents, a case study conducted at PT Asuransi Allianz Utama Indonesia Semarang Branch. This study selected a sample of 100 respondents using the simple random sampling technique and the probability sampling method. Data was collected through observation, interviews, literature review, and questionnaires. The Agree-Disagree Scale with a scoring range of 1-10 was used in this research. The data were analyzed using descriptive analysis, research instrument tests, and multiple regression analysis methods. Hypothesis testing was conducted using the F-test, t-test, and coefficient of determination test. The results regarding the respondents' characteristics showed that the majority of respondents were females aged 31-40 with a bachelor's degree as their highest educational background. Most respondents had been working as general insurance agents at PT Asuransi Allianz Utama for 1-2 years, primarily in the Semarang agency region. Descriptive analysis results indicated that all indicators of the variables job training (X1), commission (X2), and general insurance agent performance (Y) had high interpretations within the range of 42.9 - 61.0. The instrument test results on the questionnaire data were declared valid and reliable. Multiple regression analysis yielded the equation Y = 2.523 + 0.414X1 + 0.292X2. The results of both partial and simultaneous hypothesis tests showed a significant and positive influence on general insurance agent performance. The coefficient of determination test revealed that 59.9% of the variance in general insurance agent performance was influenced by job training and commission, while 40.1% was influenced by other variables not examined in this study